POST-INTUBATION TRACHEAL INJURY - LESSONS TO BE LEARNT - DILIP GUDE; HINA MOHIUDDIN; ASLAM ABBAS (International Journal of Pharma and Bio Sciences, 2013)
Complications following traumatic intubations are devastating and could prove fatal. Extremely demanding, they necessitate that the intensivists’ team possess the adequate skill and presence of mind to tackle such complications. We discuss our experience with one such case and review the literature discerning the probable causes and prevention strategies.A 62 yr old female presented with endotracheal (ET) tube in-situ from another center where she was intubated and mechanically ventilated for 5 days for severe shortness of breath and altered sensorium secondary to gastrointestinal sepsis and right lower lobe-pneumonia. Upon admission she was hemodynamically stable and mechanical ventilatory support was continued. Her electrolyte disturbances and metabolic acidosis were corrected, along with adequate broad spectrum antibiotic coverage. There was a past history of bronchial asthma and inhaled and occasional oral corticosteroid use. Over the next 2 days she responded well and was weaned off the ventilator whilst continuing continuous positive airway pressure (CPAP) support. The next day post-extubation she developed respiratory distress that was refractory to CPAP warranting invasive ventilation again. During intubation, a 7.5mm endotracheal tube with a stylet, was advanced. Air entry was equal in bilateral apices but feeble which was interpreted as secondary to thick (obese) chest wall. Auscultation of abdomen over gastric fundus did not reflect the ambu-bag ventilation. Patient began developing rapid subcutaneous swelling beginning from the neck to face upwards and chest and trunk downwards including both the upper limbs. Due to the swelling and protrusion of tongue it was virtually impossible to advance the laryngoscope to re-guide the ET tube. Emergency tracheostomy was planned but before the procedure could start, patient developed cardiac arrest necessitating advanced cardiac-life-support protocol of cardiopulmonary resuscitation (CPR). Due to massive subcutaneous emphysema, the tracheostomy procedure failed and the patient could not be revived despite aggressive CPR. Post-humous fibreoptic bronchoscopy confirmed the tracheal tear (level II degree as per classification described below).